Possible Prophylactic Effect of Poria Mushroom Extract on Chemically-Induced Chronic Kidney Disease In Vitro and In Vivo - Wagmaister, Jonathan; Zheng, Kelvin; Choudhury, Muhammad; Eshghi, Majid; Konno, Sensuke (International Journal of Innovative Research in Medical Science, 2019)
Background: Hypothesizing that oxidative stress (OXS) could be a key pathogenic factor for the incidence of chronic kidney disease (CKD), we investigated if the Poria mushroom extract, PE, with possible antioxidant activity, would prevent the incidence of CKD in rats. Materials and Methods: Antioxidant activity of PE was examined against OXS induced by hydrogen peroxide (H2O2) in renal LLC-PK1 cells. Whether PE could prevent the development of CKD in the rat kidneys, mediated through adenine (ADN)-induced OXS, was also examined. After 2 weeks, blood and kidney specimens were collected from rats for blood, histopathologic, and biochemical analyses. Results: Although H2O2-induced OXS led to a significant cell viability reduction in LLC-PK1 cells, PE significantly diminished OXS and sustained high (~70%) cell viability. In rats, ADN-given rats showed typical renal dysfunction with palpable kidney damage; however, PE supplement improved renal function with better histology. A ~2.2-fold increased OXS level was also seen in ADN-given rats but it was reduced by ~27% with PE supplement. Moreover, analysis of kidney injury biomarkers further confirmed extended kidney damage by ADN. Nevertheless, PE effectively maintained the natural status of those markers, protecting the rat kidneys. Conclusions: OXS is indeed harmful to renal cells in vitro and could even lead to ADN-induced CKD in vivo. However, PE appears to have antioxidant activity capable of protecting renal cells and the rat kidneys from such detrimental OXS. Therefore, it is rather possible that PE could be a natural antioxidant with prophylactic effect against OXS-induced CKD.